QUIZIZZ MODE PAPER UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR SISWA PADA MATERI HAJI DAN UMRAH DI SMP - Khairiah; Nurmawati (Universitas Muhammadiyah Tangerang, 2026)
This study aimed to examine the effect of Quizizz Paper Mode on students' learning motivation and learning outcomes in the Hajj and Umrah topic at the junior high school level. The research employed a quantitative approach using a quasi-experimental method with a pretest-posttest control group design. The sample consisted of two classes: an experimental class that used Quizizz Paper Mode and a control class that received conventional assessment, with 30 students in each class. Learning motivation data were collected using a Likert-scale questionnaire, while learning outcomes were measured through pretests and posttests. Data were analyzed using descriptive and inferential statistics, including normality tests, homogeneity tests, and the Independent Sample t-Test at a significance level of 0.05. The findings revealed that Quizizz Paper Mode significantly improved students' learning motivation, as indicated by the increase in the experimental class mean score from 68.87 to 87.43, compared with the control class, which increased from 68.13 to 76.67. Students' learning outcomes also improved substantially, with the experimental class mean score increasing from 63.40 on the pretest to 89.30 on the posttest, while the control class increased from 62.97 to 77.80